Narrative counselling : social and linguistic processes of change - Muntigl, Peter (Discourse approaches to politics, society, and culture, 2004)
What actually happens in counselling interactions? How does counselling bring about change? How do clients end up producing new and alternative stories of their lives and relationships? By addressing these questions and others, Peter Muntigl explores the narrative counselling process in the context where it is enacted: the unfolding conversation between counsellor and clients. Through a transdisciplinary approach that combines conversation analysis and systemic functional linguistic theory, Muntigl demonstrates how language is used in couples counselling, how language use changes over the cour.